Urgensi Penanggulangan Kemiskinan Berbasis Kearifan Lokal di Kabupaten Aceh Utara - Ferizaldi, Ferizaldi (Sociology Department Of Syiah Kuala University, 2022)
The poverty rate in North Aceh District is still quite high, it was inversely proportional to the glory of the gas and oil industries in the past, so it once earned the nickname